Effects of non-coding RNAs and RNA-binding proteins on mitochondrial dysfunction in diabetic cardiomyopathy - Potel, Koray N.; Cornelius, Victoria A.; Yacoub, Andrew; Chokr, Ali; Donaghy, Clare L.; Kelaini, Sophia; Eleftheriadou, Magdalini; Margariti, Andriana (Frontiers in Cardiovascular Medicine, 2023)
Vascular complications are the main cause of diabetes mellitus-associated morbidity and mortality. Oxidative stress and metabolic dysfunction underly injury to the vascular endothelium and myocardium, resulting in diabetic angiopathy and cardiomyopathy. Mitochondrial dysfunction has been shown to play an important role in cardiomyopathic disruptions of key cellular functions, including energy metabolism and oxidative balance. Both non-coding RNAs and RNA-binding proteins are implicated in diabetic cardiomyopathy, however, their impact on mitochondrial dysfunction in the context of this disease is largely unknown. Elucidating the effects of non-coding RNAs and RNA-binding proteins on mitochondrial pathways in diabetic cardiomyopathy would allow further insights into the pathophysiological mechanisms underlying diabetic vascular complications and could facilitate the development of new therapeutic strategies. Stem cell-based models can facilitate the study of non-coding RNAs and RNA-binding proteins and their unique characteristics make them a promising tool to improve our understanding of mitochondrial dysfunction and vascular complications in diabetes.